Performance in the Licensure Examination for Teachers (LET) for Bachelor of Technical-Vocational Teacher Education (BTVTEd): A Proposed LEPT Strategic Review and Coaching Program - Buraga, Mary Grace; Batoon, Nerissa (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the predictors of Licensure Examination for Teachers (LET) performance among Bachelor of Technical-Vocational Teacher Education (BTVTEd) graduates of Isabela State University as basis for a proposed LEPT Strategic Review and Coaching Program. Anchored on an Independent Variable–Dependent Variable framework, the study considered demographic attributes, educational background, and academic and support services as predictor variables, while LET performance in General Education, Professional Education, Field of Specialization, and Overall Rating served as outcome variables. The study employed a descriptive-correlational design with quantitative and qualitative components. Using purposive sampling, 150 BTVTEd graduates from ISU Angadanan, ISU Ilagan, and ISU San Mateo were surveyed through a structured questionnaire, with qualitative insights gathered from open-ended responses. Findings showed that graduates generally had good academic performance and rated the university’s curriculum, instruction, faculty performance, library, laboratory, and guidance services as excellent. However, LET performance was only fair in General Education and below fair in Professional Education, Field of Specialization, and Overall Rating. Significant differences were observed in selected demographic and educational variables, while most predictor variables were not significantly related to overall LET performance. Regression results identified academic experience as a predictor of Professional Education performance, parents’ monthly income as a predictor of Field of Specialization performance, and campus attended as a predictor of Overall LET Rating. Top-performing graduates attributed their success to review center enrollment, self-directed study, online resources, and institutional review sessions, while broad specialization coverage, time pressure, and anxiety emerged as major challenges. The study recommends a structured, competency-based, and equity-oriented LEPT Strategic Review and Coaching Program. The study supports SDG 4, SDG 8, SDG 10, and SDG 17 by promoting quality teacher education, employability, equitable academic support, and institutional collaboration. Its sustainability impact lies in strengthening educational quality, institutional accountability, and technical-vocational teacher preparation.
Keywords: Academic Support Services; BTVTEd Graduates; Field of Specialization; LEPT Strategic Review; Coaching Program; LET Performance; Predictors of Performance; Technical-Vocational Teacher Education; Teacher Licensure